Fatal fever : tracking down Typhoid Mary - Jarrow, Gail (Deadly diseases trilogy., 2021)
Chronicles the tracking of a New York City outbreak of typhoid fever in the early 1900s and the efforts of local public health officials to stop the spread and pinpoint the source of the outbreak, which ended up being Irish immigrant Mary Mallon, an asymptomatic carrier of the bacteria that caused the disease. Includes photographs, sidebars, a list of famous typhoid victims, a glossary, a timeline, and a list of additional resources.